Sistem Penyusunan dan Penerapan Qanun pada Masa Sultan Sulaiman Al Qanuni dan Pemerintahan Otonomi Aceh - Qurratul Aini (TANFIDZIY, 2022)
During the Ottoman era, and during the reign of Sultan Sulaiman (926-974 H/1520-1560), Islamic law began to be applied in a more definite manner, as the Qanun has become official law of his country. Aceh is one of the provinces in the Unitary Republic of Indonesia, where the province of Aceh is legally granted special autonomy through law number 11 of 2006 concerning the governance of Aceh. The aim of this research is to compare the qanun system during the reign of Sultan Sulaiman al-Qanuni with qanun aceh. This study makes use of qualitative research, especially libertarian literature (research), which relates to a normative legal approach. In the meantime, the major data sources in Turkey and Aceh refer to secondary data in the form of laws/Qanuns. According to the findings of this study, the Qanun drafting system in Turkey refers to: 1. establishing an official state school of thought Developing a single viewpoint, a school of thought 3. Complicated from several schools of thought and adopting current laws, which is used in Turkey, as for the establishment of the law, could not be separated from religious scholars and the Grand Mulfis. Whereas in Aceh, the mechanism for producing legal material that is considered in phases involves a large number of specialists from a variety of fields, including fiqh law, in the form of legislation established jointly with the executive and legislative (the Governor and the DPRK). According to the requirements of articles 21 and 22 of law number 11 of 2006 addressing the governance of Aceh, the Aceh qanun is a statutory regulation akin to a province regional regulation that governs the administration of government and the lives of the people of Aceh.